Giant Lipoma of Posterior Cervical Region - Mahendra Singh; Ashish Saxena; Lovekesh Kumar; Snehal K. Karande; Yuvraj Kolhe (Case Reports in Surgery)
Lipomas are the slow growing soft tissue tumors of benign nature. They commonly grow on torso and extremities but may also develop in head and neck region. Rarely lipomas can grow to acquire gigantic proportions, turning into an entity termed as giant lipoma. Such lipomas are entitled to immediate attention as they have a relatively high malignant potential. We report a rare case of giant cervical lipoma in an elderly gentleman, followed by a brief discussion on diagnosis and management of the disorder.